Predictors of growth patterns in children with mucopolysaccharidosis I after haematopoietic stem cell transplantation. Issue 4 (26th April 2022) - Maier, Stefanie; Zivicnjak, Miroslav; Grigull, Lorenz; Hennermann, Julia B.; Aries, Charlotte; Maecker‐Kolhoff, Britta; Sauer, Martin; Das, Anibh M.; Beier, Rita
Abstract: Mucopolysaccharidosis type I (MPS I) is an autosomal‐recessive metabolic disorder caused by an enzyme deficiency of lysosomal alpha‐l ‐iduronidase (IDUA). Haematopoietic stem cell transplantation (HSCT) is the therapeutic option of choice in MPS I patients younger than 2.5 years, which has a positive impact on neurocognitive development. However, impaired growth remains a problem. In this monocentric study, 14 patients with MPS I (mean age 1.72 years, range 0.81–3.08) were monitored according to a standardised follow‐up program after successful allogeneic HSCT. A detailed anthropometric program was carried out to identify growth patterns and to determine predictors of growth in these children. All patients are alive and in outpatient care (mean follow‐up 8.1 years, range 0.1–16.0). Progressively lower standard deviation scores (SDS) were observed for body length (mean SDS −1.61; −4.58 – 3.29), weight (−0.56; −3.19 – 2.95), sitting height (−3.28; −7.37 – 0.26), leg length (−1.64; −3.88 – 1.49) and head circumference (0.91; −2.52 – 6.09). Already at the age of 24 months, significant disproportions were detected being associated with increasing deterioration in growth for age. Younger age at HSCT, lower counts for haemoglobin and platelets, lower potassium, higher donor‐derived chimerism, higher counts for leukocytes and recruitment of a matched unrelated donor (MUD) positively correlated with body length ( p  ≤ 0.05). In conclusion, this study characterised predictors and aspects of growth patterns in children with MPS I after HSCT, underlining that early HSCT of MUD is essential for slowing body disproportion.